Development of a two-stage thermoacoustic refrigerator prototype - Samir Gh. Yahya; Ahmed Hamood; Artur J. Jaworski; Xiaoan Mao (International Journal of Thermofluids)
A traveling-wave thermoacoustic refrigerator is a potential cooling option for electronics enclosures. The main advantage of this type of refrigerator is the lack of moving parts, which makes it a maintenance-free application. The design and laboratory implementation of a travelling-wave thermoacoustic refrigerator is studied and presented in this paper. The matching between the thermoacoustic refrigerator and a pair of linear motors is investigated. A model of the refrigerator was first developed via DeltaEC simulations and then validated experimentally. A final configuration comprising of a two-stage refrigerator driven by two linear motors is presented. The model of the refrigerator runs at a frequency of 60 Hz, and it is able to generate a cooling power of 446 W at a cooling temperature of 0 °C. The setup and instrumentation of the apparatus is explained in detail. Experimentally, the refrigerator's maximum cooling load was 298 W, and the lowest cooling temperature achieved was -0.2 °C. At the maximum cooling power, the COP is 2.35.